Land survey assistance and its potential for the provision of sustainable agricultural land in East Barito District [Pendampingan survei lahan dan potensinya untuk penyediaan lahan pertanian berkelanjutan di Kabupaten Barito Timur] - S Saijo; S Septian; Imam Abdul Aziz (Buletin Pengabdian Bulletin of Community Services, 2024)
The conversion of rice paddy fields into oil palm plantations and mining sites in East Barito Regency, Central Kalimantan, poses a significant threat to the sustainability of agriculture. If this trend continues, the availability of land suitable for farming will decline. This study aims to assist local communities in the identification and management of sustainable agricultural land. The activities were conducted in Wuran Village, Karusen District, East Barito Regency, Central Kalimantan, from July to August 2024. The methods employed in this community service include interviews and assistance in soil suitability surveys as well as analysis of nutrient content at the site. Interview results indicate that 90% of respondents found the program beneficial. Soil surveys, analyzed with pH as a primary indicator, revealed a low pH of 4.5, necessitating interventions to raise it closer to the neutral pH of 6. Efforts undertaken include improving water management through the construction of bunds and the application of lime. Nutrient analysis showed that nitrogen (N), phosphorus (P), and potassium (K) levels were categorized as moderate to low. To enhance land productivity, it is recommended to increase doses of urea, SP-36, and KCl according to guidelines, along with the application of organic amendments such as straw. In conclusion, the enthusiasm of the community for the assistance provided indicates the potential for sustainable agricultural practices on their land. The findings of this study are expected to serve as a reference for the development of more sustainable agricultural strategies in the region.